2022
DOI: 10.52622/jcar.v1i2.92
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Accompaniment Music on the Concentration and Learning Outcomes of Grade VIII Students in Alpha Omega Education Tutoring Center

Abstract: Feeling fed up and bored in learning mathematics occurs because of the imbalance between the right brain and the left brain, by forcing the brain to work very hard, can cause fatigue in the brain which results in a decrease in the concentration of students, especially mathematics. One method that can be used to increase concentration that can make the brain can relax in learning mathematics is to listen to classical music. The results of this study showed that there was a difference in the average grade of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…This indicates that employing songs as a learning medium can enhance students' vocabulary, particularly in the areas of nouns and verbs. The result of this study is also in line with the previous study conducted by Tampubolon & Tamba (2022) which showed that listening to songs such as classical music can improve students' learning outcomes and concentration.…”
Section: Finding and Discussionsupporting
confidence: 90%
“…This indicates that employing songs as a learning medium can enhance students' vocabulary, particularly in the areas of nouns and verbs. The result of this study is also in line with the previous study conducted by Tampubolon & Tamba (2022) which showed that listening to songs such as classical music can improve students' learning outcomes and concentration.…”
Section: Finding and Discussionsupporting
confidence: 90%